The Effect of Cost Accounting Information on Islamic Social Reporting Disclosure of Indonesia Sharia Listed Companies - Muhammad Adi Wicaksono (Journal of Islamic Economics Lariba, 2021)
The focus of this study is to determine the factors that affect the level of disclosure of Islamic Social Reporting (ISR) in sharia public companies that constituent of Jakarta Islamic Index (JII) in the 2016-2017 period. The sample is selected using purposive sampling method, obtained a sample 26 companies. Methods of data analysis in this research using multiple linear regression, t test, F test, classic assumption and the coefficient of determination. This result shows that the number of commissioner has positive significant influences to ISR. The portion of Cost Of Good Sold (COGS) against total operational cost, has positive significant influences to ISR. While firm size has no effect at all on ISR disclosure level. The findings conclude that operational cost take significant factor to ISR. The sharia public companies should give more attention to share the important of cost accounting information. The sharia investor in Indonesia needs sufficient disclousure of operational cost structure of sharia public companies.